"Love Dem Bad": Embodied Experience, Self‐Adoration, and Eroticism in Dancehall. Issue 2 (9th November 2017) - McCoy‐Torres, Sabia
Abstract: Based on fieldwork in a West Indian community in Brooklyn, New York, this article examines women's presentations of gender and sexuality in "dancehall" reggae dance. While scholarship concerning Black women in popular performance has examined hypersexual representations, it is also important to expand analyses to understand how women are empowered by their bodies through movement, subjectivity, and ecstatic experience. Using dancehall dance as an ethnographic lens, this article demonstrates how scholarship can take into account evolving interpretations of self‐presentation to understand nuances of power, movement, embodied experience, and subjectivity. In doing so, it re‐imbues Black women's bodies with agency rather than just positioning them as passive objects of historic violence and sexualization. By valuing dancehall dance as a site to celebrate the body's diverse physicality, the article interprets how bodies attain sensuous experience anchored both in self‐adoration, and kinesthetic pleasure, which I describe as, "introspective eroticism." Here, we can also see how signifying gender difference becomes a means through which women assert themselves within male‐dominated reggae spaces and how physical experience can transform bodies from objects into subjects.